A MODEL FOR MANAGING BUSINESS ECONOMIC SECURITY IN THE DIGITAL ECONOMY: A RISK-CONTROL MATRIX AND A KRI/KPI INDICATOR SYSTEM - Венцурик, Аліса (SWorldJournal, 2026)
Introduction. Digital transformation changes the nature of business economic security: data, digital platforms, integrations, cloud and outsourced services become critical assets, while incident-driven disruptions increasingly translate into direct and in